PENINGKATAN PRODUKSI PADI MELALUI PEMANFAATAN LAHAN SUBOPTIMAL DI DESA BANJARANYAR KECAMATAN BREBES - Mardiyanti, Titik; Rajiman; Tri Wibowo, Haris (Journal of Agribusiness and Community Development (AGRIVASI) UMUS, 2023)
This study aims to determine the increase in rice production with sub-optimal land use in the Makmur I Farmer Group in Banjaranyar Village. The research method used is survey. The sampling technique was purposive sampling, with a total sample of 30 respondents belonging to the Makmur I Farmer Group. Data analysis used descriptive analysis using a Likert scale tool. The results showed that there was an increase in rice production on sub optimal land. Increased rice production in sub-optimal land occurs due to the application of technology, namely tillage with tractors, pumping irrigation technology, use of superior and early maturing varieties, use of balanced fertilizers with organic fertilizers, and adjusting cropping patterns